HUBUNGAN STRES DENGAN GANGGUANG SIKLUS MENSTRUASI PADA REMAJA PUTRI SMP SWASTA TELADAN PEMATANGSIANTAR - Firdasari Firdasari (GLOBAL HEALTH SCIENCE, 2020)
Menstruation is a natural process of women which is the decay of the endometrial wall that exits through the vagina along with blood, a normal menstrual cycle of 21-35 days. Menstrual cycle disorders are affected by disturbances in hormone funection , systemic abnormalities, stress, adenoids, and excessive prolactin hormone. Nowaday, there are many facts that reveal the relationship between stress and menstruation which is a health problem. The purpose of this study was to determine the relationship of stress with menstrual cycle disorders in young women in pematangsiantar TELADAN school SMP in 2018. The method used was analytical survey method with cross sectional approach. The population of this study was 53 students in grade 3 at SMP Swasta TELADAN Pematangsiantar, with a total sampling technique. The sampel in this study amounted to 47 people. Data analysis, namely univariate analysis was conducted to find out the description of respondents according to the variables studied in the form of frequency distribution tables, while bivariate analysis used the chi-square test. The results at the end of the study found that 31 respondents (66,0%) experienced svere stress with details of 18 respondents (58,1%) with normal menstrual cycle and 13 respondents (14,9%) with abnormal mentrual cycles (polimenorea). Value p=0,035 (p